Insights Into Chloroplast Genome Evolution Across Opuntioideae (Cactaceae) Reveals Robust Yet Sometimes Conflicting Phylogenetic Topologies - Köhler, Matias; Reginato, Marcelo; Souza-Chies, Tatiana Teixeira; Majure, Lucas C. (Frontiers in Plant Science, 2020)
Chloroplast genomes are frequently treated as highly conserved among plants. However, many lineages of vascular plants have experienced structural rearrangements, including inversions and modifications to the size and content of genes. Cacti are one of these lineages, containing the smallest plastome known for an obligately photosynthetic angiosperm, including the loss of one copy of the inverted repeat and the ndh gene suite, but only a few cacti from the subfamily Cactoideae have been characterized. Here, we investigated the variation of plastome sequences across the second-major lineage of the Cactaceae, the subfamily Opuntioideae, to address 1) how variable is the content and arrangement of chloroplast genome sequences across the subfamily, and 2) how phylogenetically informative are the plastome sequences for resolving major relationships among the clades of Opuntioideae. Our de novo assembly of the Opuntia quimilo plastome recovered an organelle of 150,347 bp in length with both copies of the inverted repeat and the presence of all the ndh gene suite. An expansion of the large single copy unit and a reduction of the small single copy unit was observed, including translocations and inversion of genes as well as the putative pseudogenization of some loci. Comparative analyses among all clades within Opuntioideae suggested that plastome structure and content vary across taxa of this subfamily, with putative independent losses of the ndh gene suite and pseudogenization of genes across disparate lineages, further demonstrating the dynamic nature of plastomes in Cactaceae. Our plastome dataset was robust in resolving three tribes with high support within Opuntioideae: Cylindropuntieae, Tephrocacteae and Opuntieae. However, conflicting topologies were recovered among major clades when exploring different assemblies of markers. A plastome-wide survey for highly informative phylogenetic markers revealed previously unused regions for future use in Sanger-based studies, presenting a valuable dataset with primers designed for continued evolutionary studies across Cactaceae. These results bring new insights into the evolution of plastomes in cacti, suggesting that further analyses should be carried out to address how ecological drivers, physiological constraints and morphological traits of cacti may be related with the common rearrangements in plastomes that have been reported across the family.